2016
DOI: 10.1016/j.jjcc.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Prosthesis–patient mismatch due to small ring annuloplasty in patients with degenerative mitral insufficiency

Abstract: Mitral valve repair results in excellent clinical outcomes with significant reductions in MI, LAD, and TRPG for all sizes of prosthesis. However, use of a smaller prosthesis may result in a higher mean transmitral pressure gradient, and may inhibit reverse remodeling of the left atrium. Therefore, PPM should be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…A smaller mitral annuloplasty ring may cause functional mitral stenosis and late-onset AF after MV repair for type II dysfunction. [17][18][19] Therefore, the annuloplasty ring size was significantly larger in the MICS group than in the sternotomy group. Notably, a minimally invasive approach did not significantly increase residual post-repair MR.…”
Section: Discussionmentioning
confidence: 92%
“…A smaller mitral annuloplasty ring may cause functional mitral stenosis and late-onset AF after MV repair for type II dysfunction. [17][18][19] Therefore, the annuloplasty ring size was significantly larger in the MICS group than in the sternotomy group. Notably, a minimally invasive approach did not significantly increase residual post-repair MR.…”
Section: Discussionmentioning
confidence: 92%
“…In fact, the size of the prosthetic ring was significantly smaller in patients with late Af than in those without Af in multivariate analysis. We have recently shown that a smallersized prosthesis can cause functional mitral stenosis at the time of mitral valve repair for type II dysfunction [20]. Additionally, functional mitral stenosis after mitral valve repair may occur in patients who receive small annuloplasty rings with subsequent pannus overgrowth, gradually reducing the mitral valve orifice area over time [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] An annuloplasty ring is an essential part of mitral valve repair procedures to remodel the annulus and consequently stabilize the repair for long-term durability. We previously reported 10 that a small-sized prosthesis for mitral valve repair may result in prosthesis-patient mismatch and thus, a largesized prosthesis should be placed. However, the influence of the type of annuloplasty prosthesis on long-term durability has not been fully established.…”
Section: See Editorial Commentary Page 1925mentioning
confidence: 99%